Synergistic adhesion strategies for solid electrolyte membranes
By combining solid electrolyte particles, ion-conducting polymer electrolyte and chopped nanofibers in the solid electrolyte separator of solid lithium-ion batteries, the problem of reducing ionic conductivity when the solid battery separator increases flexibility is solved, and high ionization is achieved Separators with electrical conductivity and excellent mechanical properties simplify the battery packaging process.
Patent Information
- Application Number
- CN202411056288.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-16
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-25
AI Technical Summary
The solid electrolyte separators in existing solid-state lithium-ion batteries often reduce ionic conductivity while increasing flexibility, affecting the performance of the battery.
By combining solid electrolyte particles, ion-conducting polymer electrolytes and chopped nanofibers in the membrane of solid electrolyte separators, the synergistic action of these materials is used to improve the flexibility and mechanical strength of the separators while maintaining high ionic conductivity.
The high ionic conductivity and excellent mechanical properties of solid-state battery separators, including good flexibility and higher strength, simplifies the battery packaging process and reduces operating stacking pressure.
Smart Images

Figure CN119518227A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to solid electrolyte separators in solid-state batteries. Background Art
[0002] Lithium-ion batteries conventionally contain a liquid electrolyte used in conjunction with a porous polymer membrane. Solid-state batteries offer an alternative to conventional lithium-ion batteries. Typically, a solid-state lithium-ion battery includes a solid electrode and a solid electrolyte that separates the electrodes. A solid electrolyte is an alternative to a liquid electrolyte. A solid electrolyte typically has a sufficiently high ionic conductivity to be used in electrochemical applications, but it is rigid or non-flexible. Batteries with flexible solid electrolytes may allow for easier mass production and incorporation into wound electrochemical cells. However, methods used to increase the flexibility of the solid electrolyte separator may affect ionic conductivity. Summary of the invention
[0003] According to one embodiment, a solid electrolyte separator is provided, the solid electrolyte separator comprising a membrane. The membrane comprises solid electrolyte particles, the solid electrolyte particles being bound together by an ion-conducting polymer electrolyte and mechanically interlocked by chopped non-polar nanofibers.
[0004] In an alternative embodiment, a solid electrolyte separator is provided, the solid electrolyte separator comprising a membrane. The membrane comprises solid electrolyte particles, the solid electrolyte particles being bound together by an ion-conducting polymer electrolyte. The membrane also comprises short-cut polar polymer nanofibers, the short-cut polar polymer nanofibers mechanically interlocking the solid electrolyte particles together and comprising polar functional groups, the polar functional groups generating intermolecular forces that attract the solid electrolyte particles. In yet another embodiment, a battery comprises a negative electrode, a positive electrode, and a solid electrolyte separator, the solid electrolyte separator being located between the negative electrode and the positive electrode and in contact with the negative electrode and the positive electrode. The solid electrolyte separator has a membrane, the membrane comprising solid electrolyte particles, an ion-conducting polymer electrolyte that binds the solid electrolyte particles together, and short-cut nanofibers that mechanically interlock the solid electrolyte particles together. BRIEF DESCRIPTION OF THE DRAWINGS
[0005] Figure 1 is a schematic perspective view of an exemplary solid electrolyte separator according to an embodiment.
[0006] Figure 2 is a schematic perspective view of an exemplary solid electrolyte separator according to another embodiment.
[0007] Figure 3 is a cross-sectional view of a battery device including an exemplary solid electrolyte separator. DETAILED DESCRIPTION
[0008] As required, detailed embodiments of the present invention are disclosed herein; however, it should be understood that the disclosed embodiments are merely examples of the present invention that can be implemented in various forms and alternative forms. The drawings are not necessarily drawn to scale; some features may be enlarged or minimized to show details of specific components. Therefore, the specific structural details and functional details disclosed herein are not to be interpreted as limiting, but only as a representative basis for teaching those skilled in the art to adopt the present invention in various ways.
[0009] Inorganic solid electrolytes are components in solid-state lithium-ion batteries, and examples of the inorganic solid electrolytes may include oxide-type, sulfide-type, or halide-type solid electrolytes. Sulfide-type electrolytes (particularly but not limited to argyrodite) are promising candidates for solid-state batteries due to the high ionic conductivity of sulfides and the mechanical properties that make sulfides easy to manufacture.
[0010] To make a lab-scale prototype battery, the solid electrolyte powder can be cold pressed to form a pellet, which can then be pressed between an anode electrode and a cathode electrode to make a solid-state battery. The disadvantage of a pellet-type separator is that it is not suitable for mass production. To easily adapt to current large-scale lithium-ion battery manufacturing, the solid electrolyte powder can be processed into a sheet separator instead. It is preferred that the sheet be as thin as possible to compete with conventional non-solid-state lithium-ion batteries in terms of energy and power density.
[0011] Binder materials can be used to hold solid electrolyte particles together as a separator sheet. However, conventional binders typically reduce the ionic conductivity of the separator sheet by disrupting the lithium ion conduction path. Therefore, it is preferred to use a minimum amount of binder while still achieving the desired separator properties.
[0012] The production of solid electrolyte separator sheets using a slurry process may include calendering the sheet at very high pressures to produce sufficient solid electrolyte particle contact and high lithium ion conduction across particle interfaces. The pressure may be as high as 300 MPa to 500 MPa. Preferred solid electrolyte separators may be fully compacted, exhibiting a very smooth glassy surface.
[0013] However, high pressure calendering can add complexity by changing the morphology of the binder material and negatively affecting ionic conductivity. It has been found that the ionic conductivity of sulfide separators decreases with increasing calendering. As calendering, and therefore pressure, increases, the particle contacts in the separator sheet change due to the binder morphology changing during compression. This can occur for many binder materials, as most polymer binders currently used tend to cover a large portion of the surface of the solid electrolyte particles in the separator sheet.
[0014] The contact between the binder material and the solid electrolyte particles can be controlled by controlling the morphology of the binder material. A filament-shaped binder can be used to minimize contact with the active solid electrolyte particles. Thus, a flexible, strong, thin solid electrolyte separator sheet can be produced by utilizing the synergistic effect of a filament-shaped binder and an ion-conducting binder.
[0015] The filament type adhesive may include nanofibers or microfibers. Commercially available microfibers may include polypropylene fibers (PPF), cellulose fibers, glass fibers, or carbon nanofibers. More advanced nanofibers and microfibers may be made by electrostatic spinning processes. The example of advanced fibers may include polytetrafluoroethylene (PTFE) fibers, polyvinylidene fluoride (PVDF) fibers, fluorinated ethylene-propylene (FEP) fibers, and other fluoropolymer fibers, or other fibers, such as polyacrylonitrile (PAN) fibers, polyethylene oxide (PEO) fibers, polyethylene terephthalate (PET) fibers, and other similar materials.
[0016] An exemplary method of further controlling the morphology of the binder material includes chopping or cutting the nanofiber binder material to control the length of the fibers. In one embodiment, the length of the nanofibers may be in the range of 1 μm to 1 mm. In another embodiment, the length may be in the range of 1 μm to 300 μm. In yet another embodiment, the length may be in the range of 5 μm to 100 μm.
[0017] Another exemplary way to further control the morphology of the binder material includes controlling the diameter of the nanofibers. It should be understood that the measured values of the diameter disclosed herein may not necessarily be accurate for each fiber in the sample. Instead, the reference to the diameter refers to the average diameter or D50 of the fibers that make up the sample. In one embodiment, the diameter of the nanofibers may be in the range of 0.1 μm to 10 μm. In another embodiment, the diameter may be in the range of 0.2 μm to 5 μm. In yet another embodiment, the diameter may be in the range of 0.4 μm to 2 μm.
[0018] The ion-conducting binder may include a polymer electrolyte and may provide two functions. It may bind the solid electrolyte particles together, which may increase the mechanical strength of the separator sheet; and facilitate ion transport across the solid electrolyte particles, which may reduce grain boundary resistance within the separator sheet. Non-limiting examples of ion-conducting polymer electrolytes may include in-situ formed polyethylene oxide-based polymer electrolytes.
[0019] In one embodiment, the solid electrolyte separator sheet may include 0.5 wt % to 10 wt % of chopped nanofibers, 0.5 wt % to 20 wt % of ion-conducting polymers, and 70 wt % to 99 wt % of solid electrolyte particles. In another embodiment, the solid electrolyte separator sheet may include 1 wt % to 7 wt % of chopped nanofibers, 1 wt % to 10 wt % of ion-conducting polymers, and 83 wt % to 98 wt % of solid electrolyte particles. In yet another embodiment, the solid electrolyte separator sheet may include 2 wt % to 5 wt % of chopped nanofibers, 2 wt % to 5 wt % of ion-conducting polymers, and 90 wt % to 96 wt % of solid electrolyte particles.
[0020] In one example, a solid electrolyte separator sheet may include solid electrolyte particles, a non-polar polymer nanofiber binder, and a polymer electrolyte ion-conducting binder. The non-polar nanofiber binder may be bonded to the active solid electrolyte particles by mechanical interlocking, wherein the fibers may contact several solid electrolyte particles and form a mechanically interlocked particle network. The non-polar nanofiber binder may include commercially available materials such as glass fibers or polypropylene microfibers, or materials manufactured via electrospinning such as PTFE, PVDF, or other fluoropolymers. The polymer electrolyte ion-conducting binder may facilitate ion transport across solid electrolyte particles, thereby reducing grain boundary resistance; and bond the solid electrolyte particles together, thereby increasing the mechanical strength of the separator sheet.
[0021] In another example, a solid electrolyte separator sheet may include solid electrolyte particles, a polar nanofiber binder, and a polymer electrolyte ion-conducting binder. The polar nanofiber binder may be a polar polymer, including but not limited to PAN fibers or PEO fibers made by electrospinning, or commercially available cellulose fibers. The polar nanofiber binder may bond the active solid electrolyte particles through a variety of interactions, which may include mechanical interlocking through contact, chemical bonding, or electrostatic forces across several solid electrolyte particles. The effect of the multiple interactions with the solid electrolyte particles may be a stronger bond between the separator sheets. If the separator sheet includes a sulfide-type solid electrolyte, a polar nanofiber binder having a cyanide functional group may be selected to take advantage of the possibility of interacting with the sulfide.
[0022] Acrylonitrile rubber (NBR) or hydrogenated butadiene rubber (HNBR) have been used as elastic binders in some solid electrolyte separators. They are not yet used as filament type binders, because their glass transition temperature has prevented NBR and HNBR from being made into fibers separately below room temperature. However, NBR and HNBR can be mixed with other fiber-forming materials to make mixed nanofibers, and example is NBR / Nomex nanofiber. Rubber nanofiber provides the elasticity lacking in the fiber of non-rubber blending or non-rubber coating, and this can further affect the mechanical properties of the electrolyte separator sheet comprising solid electrolyte particles, polar nanofiber binders and polymer electrolyte ion-conducting binders.
[0023] Solid electrolyte separator sheets can be manufactured using a slurry process. The slurry can include inorganic solid electrolyte particles, a nanofiber binder suspension, and an ion-conducting polymer electrolyte. In addition to slurry processing, dry milling can also be explored.
[0024] The solid electrolyte separator disclosed herein can provide high ionic conductivity greater than 1mS / cm and excellent mechanical properties, including good flexibility and higher strength than conventional solid electrolyte separators. It can also be manufactured using a fast and robust manufacturing method. In addition, such a solid electrolyte separator can reduce the degree of densification required in lithium-ion battery packaging, which can reduce the necessary operating stacking pressure to less than 1MPa. This can increase the flexibility of the separator and allow greater interface contact between the separator and the electrode, and simplify the battery packaging process.
[0025] Figure 1 An exemplary solid electrolyte separator sheet 10 according to an embodiment is schematically depicted. The separator sheet 10 includes solid electrolyte particles 12, an ion-conducting polymer electrolyte binder 14 that binds the solid electrolyte particles 12 together, and chopped non-polar nanofibers 16 that mechanically interlock the solid electrolyte particles 12 together. The solid electrolyte particles 12 may include an oxide-type, sulfide-type, or halide-type electrolyte. A non-limiting example of a sulfide-type solid electrolyte is argyrodite (Ag8GeS6). The ion-conducting polymer electrolyte binder 14 may include an in-situ formed polyethylene oxide-based polymer electrolyte. The chopped non-polar nanofibers 16 may include commercially available materials, such as glass fibers or polypropylene microfibers, or materials manufactured via electrospinning, such as PTFE, PVDF, or other fluoropolymers.
[0026] Figure 2An exemplary solid electrolyte separator sheet 20 according to another embodiment is schematically depicted. The separator sheet 20 includes solid electrolyte particles 22, an ion-conducting polymer electrolyte 24 that binds the solid electrolyte particles 22 together, and short-cut polar polymer nanofibers 26 that mechanically and electrochemically interlock the solid electrolyte particles 22 together. The solid electrolyte particles 22 may include an oxide-type, sulfide-type, or halide-type electrolyte. The ion-conducting polymer electrolyte binder 24 may include an in-situ formed polyethylene oxide-based polymer electrolyte. The short-cut polar polymer nanofibers 26 may include PAN fibers or PEO fibers made by electrospinning, commercially available cellulose fibers, or mixed rubber blends or rubber-coated nanofibers. The short-cut polar nanofibers 26 contain functional groups 28 that generate intermolecular attraction between the solid electrolyte particles 22 and the short-cut polar nanofibers 26. The functional groups 28 may include cyanide groups or ethylene oxide groups.
[0027] Figure 3 3 is a cross-sectional view of an exemplary battery device 30. According to an embodiment, the battery device 30 includes a negative electrode 32, a positive electrode 34, and a solid electrolyte separator 36. The negative electrode 32 is an electrode containing a material undergoing an oxidation reaction in which atoms release electrons during operation, and may include a carbon material such as graphite or lithium metal. The positive electrode 34 is an electrode containing a material undergoing a reduction reaction in which atoms gain electrons during operation, and may include a lithium metal oxide. The solid electrolyte separator 36 includes a membrane including solid electrolyte particles, an ion-conducting polymer electrolyte that binds the solid electrolyte particles together, and chopped nanofibers that mechanically interlock the solid electrolyte particles together. The ion-conducting polymer electrolyte may include an in-situ formed polyethylene oxide-based polymer electrolyte.
[0028] In one embodiment, the chopped nanofibers can be chopped non-polar nanofibers, including glass fibers, polypropylene microfibers, PTFE, PVDF or other fluoropolymer fibers. In another embodiment, the chopped nanofibers can be chopped polar polymer nanofibers, including PAN fibers, PEO fibers, cellulose fibers or mixed rubber blends or rubber coated nanofibers.
[0029] Although exemplary embodiments are described above, these embodiments are not intended to describe all possible forms of the present invention. Rather, the words used in the specification are descriptive rather than restrictive terms, and it should be understood that various changes may be made without departing from the spirit and scope of the present invention. In addition, the features of the various embodiments of implementation may be combined to form other embodiments of the present invention.
[0030] According to the present invention, there is provided a solid electrolyte separator having: a membrane comprising solid electrolyte particles, an ion-conducting polymer electrolyte binding the solid electrolyte particles together, and chopped non-polar nanofibers mechanically interlocking the solid electrolyte particles together.
[0031] According to an embodiment, the ion-conducting polymer electrolyte comprises an in-situ formed polyethylene oxide-based polymer electrolyte.
[0032] According to an embodiment, the length of the short chopped non-polar nanofibers falls within the range of 1 μm to 1 mm.
[0033] According to an embodiment, the length falls within the range of 1 μm to 300 μm.
[0034] According to an embodiment, the length falls within the range of 5 μm to 100 μm.
[0035] According to an embodiment, the diameter of the chopped non-polar nanofibers falls within the range of 0.1 μm to 10 mm.
[0036] According to an embodiment, the diameter falls within the range of 0.2 μm to 5 μm.
[0037] According to an embodiment, the diameter falls within the range of 0.4 μm to 2 μm.
[0038] According to an embodiment, the weight percentages of the membrane fall within the range of 0.5 wt % to 10 wt % of the chopped non-polar nanofibers and 0.5 wt % to 20 wt % of the ion-conducting polymer electrolyte.
[0039] According to an embodiment, the weight percentages fall within the range of 1 wt % to 7 wt % of the chopped non-polar nanofibers and 1 wt % to 10 wt % of the ion-conducting polymer electrolyte.
[0040] According to an embodiment, the weight percentages fall within the range of 2 wt % to 5 wt % of the chopped non-polar nanofibers and 2 wt % to 5 wt % of the ion-conducting polymer electrolyte.
[0041] According to an embodiment, the chopped non-polar nanofibers include at least one of glass fibers, polypropylene microfibers, polytetrafluoroethylene fibers, and polyvinylidene fluoride fibers.
[0042] According to the present invention, a solid electrolyte separator is provided, which has: a membrane, the membrane including solid electrolyte particles, an ion-conducting polymer electrolyte that binds the solid electrolyte particles together, and short-cut polar polymer nanofibers, the short-cut polar polymer nanofibers mechanically interlock the solid electrolyte particles together and contain polar functional groups, which produce intermolecular forces that attract the solid electrolyte particles.
[0043] According to an embodiment, the functional group comprises a cyanide group.
[0044] According to an embodiment, the functional group comprises an ethylene oxide group.
[0045] According to an embodiment, the ion-conducting polymer electrolyte comprises an in-situ formed polyethylene oxide-based polymer electrolyte.
[0046] According to an embodiment, the chopped polar polymer nanofibers include polyacrylonitrile fibers.
[0047] According to an embodiment, the chopped polar polymer nanofibers include polyethylene oxide fibers.
[0048] According to an embodiment, the short chopped polar polymer nanofibers include cellulose fibers.
[0049] According to the present invention, a battery is provided, the battery having: a negative electrode; a positive electrode; and a solid electrolyte separator, the solid electrolyte separator is located between the negative electrode and the positive electrode and is in contact with the negative electrode and the positive electrode, the solid electrolyte separator includes a membrane, the membrane includes solid electrolyte particles, an ion-conducting polymer electrolyte that bonds the solid electrolyte particles together, and short-cut nanofibers that mechanically interlock the solid electrolyte particles together.
Claims
1. A solid electrolyte separator, comprising: A membrane comprising solid electrolyte particles, an ion-conducting polymer electrolyte binding the solid electrolyte particles together, and chopped non-polar nanofibers mechanically interlocking the solid electrolyte particles together.
2. The solid electrolyte separator of claim 1, wherein the ion-conducting polymer electrolyte comprises an in-situ formed polyethylene oxide-based polymer electrolyte. 3 . The solid electrolyte separator according to claim 1 , wherein the length of the short-cut nonpolar nanofibers falls within the range of 1 μm to 1 mm. 4 . The solid electrolyte separator according to claim 3 , wherein the length falls within a range of 1 μm to 300 μm. 5 . The solid electrolyte separator according to claim 4 , wherein the length falls within a range of 5 μm to 100 μm. 6 . The solid electrolyte separator according to claim 1 , wherein the diameter of the chopped nonpolar nanofibers falls within the range of 0.1 μm to 10 mm. 7 . The solid electrolyte separator according to claim 6 , wherein the diameter falls within a range of 0.2 μm to 5 μm. 8 . The solid electrolyte separator according to claim 7 , wherein the diameter falls within a range of 0.4 μm to 2 μm.
9. The solid electrolyte separator of claim 1, wherein the weight percentage of the membrane falls within the range of 0.5 wt% to 10 wt% of the chopped non-polar nanofibers and 0.5 wt% to 20 wt% of the ion-conducting polymer electrolyte.
10. The solid electrolyte separator of claim 9, wherein the weight percentages fall within the range of 1 wt% to 7 wt% of the chopped non-polar nanofibers and 1 wt% to 10 wt% of the ion-conducting polymer electrolyte.
11. The solid electrolyte separator of claim 10, wherein the weight percentages fall within the range of 2 wt% to 5 wt% of the chopped non-polar nanofibers and 2 wt% to 5 wt% of the ion-conducting polymer electrolyte.
12. The solid electrolyte separator of claim 1, wherein the chopped non-polar nanofibers include at least one of glass fibers, polypropylene microfibers, polytetrafluoroethylene fibers, and polyvinylidene fluoride fibers.
13. A solid electrolyte separator, comprising: A membrane comprising solid electrolyte particles, an ion-conducting polymer electrolyte that binds the solid electrolyte particles together, and short-cut polar polymer nanofibers that mechanically interlock the solid electrolyte particles together and contain polar functional groups that generate intermolecular forces that attract the solid electrolyte particles.
14. The solid electrolyte separator of claim 13, wherein the functional group comprises a cyanide group.
15. The solid electrolyte separator of claim 13, wherein the functional group comprises an ethylene oxide group.